Natural history of cyclodialysis cleft closure in pediatric closed-globe eye injuries - Marshall, Christopher; Armstrong, Mikhayla L.; Welcher, Jennifer; Serina, Anthony; Falcone, Michelle; Shah, Ankoor S. (Digital Journal of Ophthalmology, 2024)
Introduction Cyclodialysis cleft (CC) is a disruption of the ciliary body from the scleral spur, which allows aqueous humor from the anterior segment into the suprachoroidal space, leading to decreased intraocular pressure (IOP).(1) CCs may occur after ocular trauma,(2) but limited literature exists in pediatric populations. This study aims to describe the natural history of CC closure in a pediatric cohort. Methods This retrospective study queried Boston Children’s Hospital billing data (2015-2020), identifying patients ≤18 years diagnosed with hypotony, closed-globe eye injury, IOP ≤7 mm Hg, and documentation of suspected or confirmed CC. Cleft closure was defined as an IOP ≥10 mm Hg or chart documentation. Results Six patients were included, 4 identifying as male and 4 having right eye injuries. Two patients identified as African American and 4 as White. At presentation, ages ranged from 7 to 14 years (median, years). At diagnosis, IOPs ranged from 2 to 7 mm Hg, median visual acuity was 20/60 (range, 20/50 to counting fingers), and all patients had macular choroidal folds. All patients were prescribed cycloplegic agents. Cleft closure occurred at a median of 21 days (range, 8-65). Two recovery patterns were noted: a gradual increase in IOP or sudden spike in IOP, normalizing days later. All patients with the pressure spike had pain, positive visual phenomena, and required IOP-lowering treatment temporarily. At the final visit, visual acuity readings improved to a median of 20/20 (range, 20/20 to 20/50), a median IOP of 17 mm Hg (range, 10-20 mm Hg), and resolution of choroidal folds. Conclusion Patients achieved cleft closure with time and cycloplegic agents, suggesting some viability of medical therapy. However, the data highlight that an acute ocular hypertensive phase in some patients may require management. This transient IOP spike may result from temporary trabecular meshwork closure during the hypotenuse phase.